RELASI PERTEMANAN MAHASISWI BERCADAR DI FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI: FRIENDLY RELATIONSHIPS OF VEILED STUDENTS AT THE FACULTY OF MEDICINE AND HEALTH SCIENCES OF JAMBI UNIVERSITY - Yolla Andriana (Jurnal Psikologi Jambi, 2022)
ABSTRACT Introduction Students with veils are often considered quite difficult to socialize with others and tend to be introverted. Some societies have a negative response to women who wear the veil. Because of this view, it will affect the friendship relations of women who use the veil. Objective to describe of friendship relations and the factors that influence the friendship relations of veiled students at the Faculty of Medicine and Health Sciences of Jambi University. Method: This study used a qualitative method with a phenomenological approach. The Methods of the data collection are documentation and in-depth interviews. This research used Interpretative Phenomenological Analysis (IPA). The characteristics of veiled female students at the Faculty of Medicine and Health Sciences of Jambi University, the participants in this research were aged 18-24 years. Results: The description of the friendship relations between veiled female students at the Faculty of Medicine and Health Sciences of Jambi University is interaction, togetherness, similarity, mutual understanding, a sense of comfort, individual characteristics, competence, sharing and compatibility and the influencing factors consist of intensity and environment. Conclusions And Recommendation: The four participants had described the friendship relations of veiled female students with several unique features. This research is expected to be able to add the insight into friendship relations, especially for the friendship relations of veiled students. Keywords: Friendship relations, Students, Veil ABSTRAK Pendahuluan Mahasiswi bercadar seringkali dianggap kurang dalam bersosialisasi dan cenderung tertutup. Tidak sedikit juga pengguna cadar mendapat pandangan negatif dari masyarakat Karena adanya pandangan tersebut, tentu saja akan mempengaruhi relasi pertemanan dari pengguna cadar. Tujuan penelitian ini untuk melihat gambaran relasi pertemanan dan faktor yang mempengaruhi relasi pertemanan mahasiswi bercadar di Fakultas Kedokteran dan Ilmu Kesehatan (FKIK) Universitas Jambi. Metode Penelitian dengan Metode kualitatif dengan pendekatan fenomenologi. Metode pengumpulan data menggunakan dokumentasi dan wawancara mendalam. Menggunakan Interpretative Phenomenilogical Analysis (IPA). Karakteristik partisipan mahasiswi bercadar di Fakultas Kedokteran dan Ilmu Kesehatan (FKIK) Universitas Jambi, dan berusia 18-24 tahun. Hasil Gambaran relasi pertemanan mahasiswi bercadar di Fakultas Kedokteran dan Ilmu Kesehatan (FKIK) Universitas Jambi diantaranya interaksi, kebersamaan, kesamaan, saling memahami, kenyamanan, karakteristik individu, kompetensi, berbagi dan kecocokan. Adapun faktor yang mempengaruhi pertemanan terdiri dari intensitas dan lingkungan. Kesimpulan dan Saran Keempat partisipan telah menggambarkan relasi pertemanan mahasiswi bercadar dengan beberapa keunikan tersendiri. Penelitian ini diharapkan mampu menambah wawasan mengenai relasi pertemanan terkhusus untuk relasi pertemanan mahasiswi bercadar. Kata kunci: Relasi pertemanan, Mahasiswa, Cadar